Environmental Assessment of Greenhouse Gases Emission from Sheep Breeding in Vojvodina Region of Serbia - Miljan Samardžić M. (Sciendo, 2020)
The aim of this work is to show a calculation procedure for obtaining estimations for the carbon footprint of 1 kg of live weight of ewe, ram and lamb at the farm gate, taking into account regional typological features of agricultural production in agroecosystems. The methodology of carbon footprint (CF) calculation is based on the life cycle assessment (LCA) methodology developed for agricultural products. Results revealed that in modern technology of sheep breeding, 21.41 kg CO2 e was emitted on average per kg of body weight of ewe, 19.13 kg CO2 е was emitted on average per kg of body weight of ram, 3.2 kg CO2 e was emitted on average per kg of body weight of lamb. The main distinction of Vojvodina province is the low efficiency of fertiliser application on crop fields and manure management, storage and utilisation, which has as a result high emissions of nitrous oxide. This is the field where the implementation of intensive technologies of precise farming, manure handling, utilisation and management will significantly decrease GHG emission, with preserving yield of crops and quantity and quality of sheep of all categories.